2021
DOI: 10.1097/prs.0000000000008100
|View full text |Cite
|
Sign up to set email alerts
|

Topographic Anatomy of the Zygomatico-Orbital Artery: Implications for Improving the Safety of Temporal Augmentation

Abstract: Background: Anatomical knowledge of the zygomatico-orbital artery and its most relevant clinical applications is essential for ensuring the safety of filler injection into the temporal region. The purpose of this study was to provide the precise position, detailed course, and relationship with surrounding structures of the zygomatico-orbital artery. Methods: Fifty-eight patients who underwent head contrast-enhanced three-dimensional computed tomography and 10 fresh frozen cadavers were investigated. Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
15
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 15 publications
1
15
1
Order By: Relevance
“…This may be attributable to the limited resolution of CTA, which fails to visualize vessels smaller than 1.0 mm. According to the measurements by Liu et al, 24 the zygomatico-orbital artery was located 14.0 ± 3.4 mm above the midpoint of the zygomatic arch, which was close to our results of 12.8 ± 3.5 mm. Therefore, to avoid damage to the zygomatico-orbital artery when injecting into the interfascial plane of region B, it is relatively safe to inject filler within 12.8 mm above the zygomatic arch.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This may be attributable to the limited resolution of CTA, which fails to visualize vessels smaller than 1.0 mm. According to the measurements by Liu et al, 24 the zygomatico-orbital artery was located 14.0 ± 3.4 mm above the midpoint of the zygomatic arch, which was close to our results of 12.8 ± 3.5 mm. Therefore, to avoid damage to the zygomatico-orbital artery when injecting into the interfascial plane of region B, it is relatively safe to inject filler within 12.8 mm above the zygomatic arch.…”
Section: Discussionsupporting
confidence: 92%
“…According to our measurements, the zygomatico-orbital artery in type C, accounting for only 9.3% of total cases, was located 17.5 ± 6.4 mm above the jugale point and 12.8 ± 3.5 mm above the zygion point, respectively. However, Liu et al 24 reported that the zygomatico-orbital artery was identified in nearly 93% of the specimens, with a mean diameter of 1.2 ± 0.2 mm. This may be attributable to the limited resolution of CTA, which fails to visualize vessels smaller than 1.0 mm.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The mean diameter of ZOA when it entered OOM was 0.40 mm in females and 0.53 mm in males who had significantly larger values than females ( P =0.012). In some previous reports, the mean diameter of ZOA was 1.2 mm, 1.1 mm, and 2.52 mm, respectively 20–22 . The reason why our values were smaller than theirs may be that the measuring positions and tools were different.…”
Section: Discussioncontrasting
confidence: 65%
“…According to the measurements in our study, between the deep temporal fascia and the superficial temporal fascia, we suggest that it is relatively safe to inject filler within 14.0 mm (not 20.0 mm, as reported in an article published in 2014 3 ) above the zygomatic arch between the lateral orbital rim and the midpoint of the zygomatic arch. 1…”
mentioning
confidence: 99%